Epidemiology and Burden of Human Papillomavirus and Related Diseases, Molecular Pathogenesis, and Vaccine Evaluation - Kombe Kombe, Arnaud John; Li, Bofeng; Zahid, Ayesha; Mengist, Hylemariam Mihiretie; Bounda, Guy-Armel; Zhou, Ying; Jin, Tengchuan (Frontiers in Public Health, 2021)
Diagnosed in more than 90% of cervical cancers, the fourth deadliest cancer in women, human papillomavirus (HPV) is currently the most common pathogen responsible for female cancers. Moreover, HPV infection is associated with many other diseases, including cutaneous and anogenital warts, and genital and upper aerodigestive tract cancers. The incidence and prevalence of these pathologies vary considerably depending on factors including HPV genotype, regional conditions, the study population, and the anatomical site sampled. Recently, features of the cervicovaginal microbiota are found to be associated with the incidence of HPV-related diseases, presenting a novel approach to identify high-risk women through both blood and cervical samples. Overall, the HPV repartition data show that HPV infection and related diseases are more prevalent in developing countries. Moreover, the available (2-, 4-, and 9-valent) vaccines based on virus-like particles, despite their proven effectiveness and safety, present some limitations in terms of system development cost, transport cold chain, and oncogenic HPV variants. In addition, vaccination programs face some challenges, leading to a considerable burden of HPV infection and related diseases. Therefore, even though the new (9-valent) vaccine seems promising, next-generation vaccines as well as awareness programs associated with HPV vaccination and budget reinforcements for immunization are needed.